Lessons in Post-Disaster Self-Care From 9/11 Paramedics and Emergency Medical Technicians. Issue 3 (June 2019) - Smith, Erin; Walker, Tony; Burkle, Frederick M.
Abstract: Objective: The objective of this study was to explore preferred self-care practices among paramedics and emergency medical technicians (EMTs) who responded to the September 11, 2001 terrorist attack (9/11) in New York City (New York USA). Design, Setting, and Participants: Qualitative research methodology with convenience and subsequent snowball sampling was utilized. Participants were adult (at least 18 years of age) paramedics or EMTs who self-reported as responding to the 9/11 terrorist attack in New York City. Main Outcome Measures: Preferred self-care practices; participant characteristics; indications and patterns of self-care use; perceived benefits and harms; and views on appropriate availability of support and self-care services were the main outcome measures. Results: The 9/11 paramedic and EMT participants reported a delay in recognizing the need for self-care. Preferred physical self-care practices included exercise, good nutrition, getting enough sleep, and sticking to routine. Preferred psychosocial self-care practices included spending time with family and friends, participating in peer-support programs and online support forums, and routinely seeing a mental health professional. Self-care was important for younger paramedics and EMTs who reported having less-developed supportive infrastructure around them, as well as for retiring paramedics and EMTs who often felt left behind by a system they had dedicated their lives to. Access to cooking classes and subsidized gym memberships were viewed as favorable, as was the ability to include family members in self-care practices. Conclusion(s): A range of physical and psychosocial self-care practices should be encouraged among paramedic students and implemented by Australian ambulance services to ensure the health and well-being of paramedics throughout their career and into retirement.